Fabrication of Metal-Organic Framework Derived Nanomaterials and Their Electrochemical Applications - Xia, Wei (Springer Theses, Recognizing Outstanding Ph.D. Research, 2018)
This thesis systematically introduces readers to a new metal-organic framework approach to fabricating nanostructured materials for electrochemical applications. Based on the metal-organic framework (MOF) approach, it also demonstrates the latest ideas on how to create optimal MOF and MOF-derived nanomaterials for electrochemical reactions under controlled conditions. The thesis offers a valuable resource for researchers who want to understand electrochemical reactions at nanoscale and optimize materials from rational design to achieve enhanced electrochemical performance. It also serves as a useful reference guide to fundamental research on advanced electrochemical energy storage materials and the synthesis of nanostructured materials.